QUALITY OF LIFE OF CHILDREN WITH GLOMERULAR KIDNEY DISEASES - A.G. Timofeeva; I.V. Vinyarskaya; T.V. Margieva; V.V. Chernikov (Union of pediatricians of Russia, 2011)
The paper presents the results of a study of the life quality of children with chronic kidney diseases using a questionnaire Pediatric Quality of Life Inventory, which allows us to estimate the physical, emotional, social and role functioning. The authors included in the analysis the least studied in pediatric nephrology cohort of patients - children with intact renal function. According to the patients responses, regardless of the age, compared with healthy children, physical, emotional and social aspects were the lowest. In accordance with the parents responses the quality of children life have been reduced, mainly due to the physical component. The children of preschool age (5-7 years) showed the most marked reduction of all parameters of life quality. Key words: quality of life, chronic kidney disease, children. (Pediatric pharmacology. - 2011; 8 (6): 74-76).